An updated spectral representation method coupled with generalized probability density evolution method in assessing the seismic reliability of tunnels. Issue 166 (March 2023) - Wu, Yongxin; Wang, Juncheng; Zhang, Yuqi; Geng, Weijuan; Guo, Pengyun
Abstract: The dimension reduction spectral representation method (SRM) is generally employed with the generalized probability density evolution method (GPDEM) to implement the seismic reliability assessment, where a noticeable non-zero value in the mean value of ground motion would be obtained. This study proposed an updated spectral representation method (U-SRM) to improve the simulated mean values, which coupled with GPDEM to investigate the nonlinear responses and seismic reliability assessment of a tunnel. Results obtained from the numerical study were compared between SRM and U-SRM. The horizontal displacement at the tunnel crown is more conservative using U-SRM than SRM in the reliability assessment of tunnels. Results indicated that U-SRM coupled with GPDEM is an efficient method to analyze the nonlinear responses and the seismic reliability of tunnels, and could serve as a reference for tunnel design in seismically active zones. Highlights: An updated dimensional reduction spectral representation method is proposed. U-SRM coupled with GPDEM is an efficient method to do the seismic reliability of tunnels. The horizontal displacement at the tunnel crown is more conservative using U-SRM than SRM.